Single-molecule sequence detection via microfluidic planar extensional flow at a stagnation point - Dylla-Spears, Rebecca (2010)
We demonstrate the use of a microfluidic stagnation point flow to trap and extend single molecules of double-stranded (ds) genomic DNA for detection of target sequences along the DNA backbone. Mutant EcoRI-based fluorescent markers are bound sequence-specifically to fluorescently labeled ds λ-DNA. The marker-DNA complexes are introduced into a microfluidic cross slot consisting of flow channels that intersect at ninety degrees. Buffered solution containing the marker-DNA complexes flows in one channel of the cross slot, pure buffer flows in the opposing channel at the same flow rate, and fluid exits the two channels at ninety degrees from the inlet channels. This creates a stagnation point at the center of a planar extensional flow, where marker-DNA complexes may be trapped and elongated along the outflow axis. The degree of elongation can be controlled using the flow strength (i.e., a non-dimensional flow rate) in the device. Both the DNA backbone and the markers bound along the stretched DNA are observed directly using fluorescence microscopy and the location of the markers along the DNA backbone is measured. We find that our method permits detection of each of the five expected target site positions to within 1.5 kb with standard deviations of <1.5 kb. We compare the method’s precision and accuracy at molecular extensions of 68% and 88% of the contour length to binding distributions from similar data obtained via molecular combing. We also provide evidence that increased mixing of the sample during binding of the marker to the DNA improves binding to internal target sequences of dsDNA, presumably by extending the DNA and making the internal binding sites more accessible.